2018
DOI: 10.1186/s40494-018-0207-0
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of a titanium dioxide/silica white pigment on wooden Andean qeros: a cultural and chronological marker

Abstract: A white pigment found on a sub-set of polychromed wooden Andean ritual drinking cups called qeros has been characterized by X-ray diffraction, X-ray fluorescence spectroscopy and Raman spectroscopy as consisting principally of cristobalite (SiO 2 ), anatase (TiO 2 ), and α-quartz (SiO 2 ). This unexpected assemblage of minerals is like that reportedly found in an exposed titanium ore body in southern Peru, an area once part of the Inka Empire. The ore is a close match in color and composition to the white pigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 26 publications
0
18
0
1
Order By: Relevance
“…While SERS of a microscopic sample removed from the object's inner neck (S2) failed, likely due to the interference of the thick mopa mopa layer in which the dye is embedded, extraction with BF 3 and methanol followed by HPLC-PDA analysis enabled the conclusive identification of carminic acidthe main coloring component of cochineal-and some of its methylated derivatives (Additional file 2: Figure S2). This dye, also found by other researchers in a selection of Andean qeros [30,31], was particularly popular in the 16th and 17th centuries, becoming the third most profitable traded commodity from the New World for the Spanish after silver and gold, and displacing kermes as the source of luxurious crimson and scarlet textiles within 50 years of its introduction [65]. Called grana by the Spanish, it had been cultivated on Opuntia cacti from about 600 C.E.…”
Section: Pigments and Colorantsmentioning
confidence: 84%
See 2 more Smart Citations
“…While SERS of a microscopic sample removed from the object's inner neck (S2) failed, likely due to the interference of the thick mopa mopa layer in which the dye is embedded, extraction with BF 3 and methanol followed by HPLC-PDA analysis enabled the conclusive identification of carminic acidthe main coloring component of cochineal-and some of its methylated derivatives (Additional file 2: Figure S2). This dye, also found by other researchers in a selection of Andean qeros [30,31], was particularly popular in the 16th and 17th centuries, becoming the third most profitable traded commodity from the New World for the Spanish after silver and gold, and displacing kermes as the source of luxurious crimson and scarlet textiles within 50 years of its introduction [65]. Called grana by the Spanish, it had been cultivated on Opuntia cacti from about 600 C.E.…”
Section: Pigments and Colorantsmentioning
confidence: 84%
“…Whites commonly used in South American artifacts have ranged from calcium-containing minerals, such as calcite, gypsum, and apatite [61][62][63][64], to lead white [65]. Similarly, scientific analysis carried out to date on qero cups has highlighted a predominant use of lead white in the form of hydrocerussite (basic lead carbonate, 2PbCO 3 •Pb(OH) 2 ) and cerussite (neutral lead carbonate, PbCO 3 ) [5,6], along with a naturally-occurring mixture of cristobalite (SiO 2 ), anatase (TiO 2 ), and α-quartz (SiO 2 ) [30,66]. In the collection of the HSML, lead white was detected in a barniz de Pasto box dating to 1684 (Newman R, Unpublished report, 2015), and this finding appeared to support Humboldt's description of white in barniz de Pasto objects as "made imperfectly with white lead oxide" [14].…”
Section: Pigments and Colorantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Las principales fuentes de anatasa conocidas las encontramos a mayores distancias hacia el sur, en el Depósito Santa Fe en la provincia de Islay (Arequipa) (mindat.org) y notablemente en el depósito Giacomo en la provincia de Tacna (Tacna), a 600 y 800 kilómetros, respectivamente, en línea recta desde Puerto Nuevo. Este último parece ser la fuente de anatasa utilizada en los pigmentos blancos que decoran keros de madera Inca del Horizonte Tardío (Howe et al 2018). Sin embargo, tal y como nota Enrique Guadalupe, uno de los autores de este artículo, el Ti es común en las arenas de playas antiguas de Arequipa y Tacna, en la forma de óxidos de titanio.…”
Section: Observaciones Sobre La Procedencia Geológica De Los Mineraleunclassified
“…Park et al [7] successfully identified the types of trees and surface materials of a lacquered wooden coffin by using Pyrolysis/gas chromatography/mass spectrometry. In the same year, Howe et al [8] helped archaeologists analyze the pigments of a sub-set of polychromed wooden Andean ritual drinking cups called qeros and its chronological marker by means of X-ray diffraction, X-ray fluorescence spectroscopy, and Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%